The urban problems of Gazimagusa (Famagusta) and proposals for the future - Hoşkara, Şebnem Ö.; Dağlı, Uğur; Doratlı, Naciye (Elsevier, 1999)
The main aim of this article is to put forward various factors, forces, and decisions which have diversified the tendency of urban growth and which have shaped the urban pattern of the city of Gazimagusa (Famagusta)1 particularly after the war in 1974, and to offer alternative policy recommendations, some strategic planning solutions including general design proposals. These are aimed at dealing with the major problems posed by the fragmentation of the urban fabric. It stresses the post-war tendency and problems of urban growth and development, by addressing the social, cultural and demographic, as well as economic and physical changes the city has been facing since then. The paper begins with a brief historical review of the evolution of the urban pattern of the city until 1974 and identifies its urban layout at that time. With the arguments in place, the paper will then provide a framework for understanding and solving the urban problems in the city after 1974 and try to evaluate the positive and negative issues, factors and/or forces which have been shaping its urban structure. Finally, some policy recommendations for planning and design solutions are provided as a basis for the integration of developing, neglected and deteriorated quarters of the city. Particular emphasis is made on the Walled City, Maras (Varosha), Asagi Maras (Kato Varosha)2 as well as the newly developed and developing quarters, which are bringing the city towards sustainable development.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Gazimagusa; urban problems; sustainability